Aspek Psikologi Pendelegasian Manajemen dan Manajemen Biaya Pabrik Roti “Yes” di UPK PIK Pulo Gadung Jakarta Timur - Hanif Hanif; Mulyani Mulyani; Supriyanto Karya; Morryessa Brandinie (President University, 2019)
The purpose of this program is to provide assistance in order to help businesses to solve their problems in business management. The approach used is observation, interview and discussion with the business founder/owner. The place is in the one of the business unit under the Unit Pengelola Kegiatan Pusat Industri Kecil (PIK), namely ” Yes